Directional Selection of Microbial Community Reduces Propionate Accumulation in Glycerol and Glucose Anaerobic Bioconversion Under Elevated pCO2 - Ceron-Chafla, Pamela; Chang, Yu-ting; Rabaey, Korneel; van Lier, Jules B.; Lindeboom, Ralph E. F. (Frontiers in Microbiology, 2021)
Volatile fatty acid (VFA) accumulation is a sign of digester perturbation. Previous work showed the thermodynamic limitations of hydrogen and CO2 in syntrophic propionate oxidation under elevated partial pressure of CO2 (pCO2). Here we study the effect of directional selection under increasing substrate load as a strategy to restructure the microbial community and induce cross-protection mechanisms to improve glucose and glycerol conversion performance under elevated pCO2. After an adaptive laboratory evolution (ALE) process, viable cell density increased and predominant microbial groups were modified: an increase in Methanosaeta and syntrophic propionate oxidizing bacteria (SPOB) associated with the Smithella genus was found with glycerol as the substrate. A modest increase in SPOB along with a shift in the predominance of Methanobacterium towards Methanosaeta was observed with glucose as the substrate. The evolved inoculum showed affected diversity within archaeal spp. under 5 bar initial pCO2; however, higher CH4 yield resulted from enhanced propionate conversion linked to the community shifts and biomass adaptation during the ALE process. Moreover, the evolved inoculum attained increased cell viability with glucose and a marginal decrease with glycerol as the substrate. Results showed differences in terms of carbon flux distribution using the evolved inoculum under elevated pCO2: glucose conversion resulted in a higher cell density and viability, whereas glycerol conversion led to higher propionate production whose enabled conversion reflected in increased CH4 yield. Our results highlight that limited propionate conversion at elevated pCO2 resulted from decreased cell viability and low abundance of syntrophic partners. This limitation can be mitigated by promoting alternative and more resilient SPOB and building up biomass adaptation to environmental conditions via directional selection of microbial community.